SIMULASI PEMBUATAN SABUN CAIR EKSTRAK DAUN KEMANGI DAN BALSAM EUCALYPTUS OIL BAGI SISWA/I SMA/K DI KOTA BEKASI - Anindita, Reza; Nathalia, Dede Dwi; Beandrade, Maya Uzia; Putri, Intan Kurnia; Perwitasari, Melania; Harahap, Nofria Rizki Amalia (Jurnal Abdi Insani, 2024)
Discourse on the utilization of medicinal plants, which have the potential to be made into liquid soap and balsam, is very much needed for SMA and SMK students as knowledge in doing entrepreneurship in developing pharmaceutical products. Therefore, community service activities (PKM) are needed to provide knowledge and skills regarding the manufacture of liquid soap from basil and balsam extracts from Eucalyptus oil. The purpose of this PKM activity is to provide knowledge, understanding, and skills regarding the procedures for making liquid soap from extracts of basil and balsam leaves from Eucalyptus oil. This PKM activity includes the planning stages, such as making socialization flyers, materials, and videos on making soap and balm from natural ingredients. The implementation stage of providing materials and simulations for SMA/K children in Bekasi City at the STIKes Mitra Keluarga Pharmaceuticals Laboratory, Bekasi. The Evaluation Stage is in the form of taking a response score on the use of liquid soap and balsam by the PKM participants. The results of this PKM showed that there were 26 SMA/SMK students in attendance in Bekasi City, with 84.61% of SMK students dominating the participants. The preferred product was Balsam Eucalyptus oil, especially in terms of aroma, texture, and warmth. This PKM concludes that participants have a new understanding of the use of basil leaves and Eucalyptus oil for making liquid soap and balsam. The product that the participants liked was balsam Eucalyptus oil compared to basil leaf extract liquid soap.